New U-shaped Liquid Crystals Azobenzene Derived from Catechol for Photoswitching Properties - Lutfor, M. R.; Biswas, Tapan Kumar; Sarkar, Shaheen M.; M. M., Yusoff; Muhammad Nor Fazli, Abd Malek; Tschierske, Carsten (Elsevier, 2015)
A new series of liquid crystals whose molecular structure consists of a U-shaped unit as a central core and two rod-like azobenzenes as the peripheral units are synthesized. The mesomorphic properties were investigated by differential scanning calorimetry, polarizing optical microscopy and X-ray diffraction. The existence of nematic and smectic A phase was confirmed by textures and X-ray diffraction. The trans-form of azo compounds showed a strong band in the UV region at ~365 nm for the π–π* transition, and a weak band in the visible region at ~450 nm due to the n–π* transition. These molecules exhibit a strong photoisomerization behavior in which trans–cis take 50 and 55 s for compounds L4/5 and L4/6, respectively, whereas cis–trans take place almost 29 and 30 h, respectively. Long thermal back relaxation allows us to realize that optical storage devices with these materials which need longer periods.